Accelerating Ovarian Age: Cancer Treatment in the Premenopausal Woman - Letourneau, Joseph; Chan, S. W.; Rosen, Mitchell P. (Seminars in Reproductive Medicine, 2013)
The reproductive sequelae of cancer treatments may provide an important model of accelerated ovarian aging. Tens of thousands of women treated for cancer each year experience infertility and early menopause as a result of treatment. A spectrum of reproductive compromise commonly ranges from immediate menopause at the time of cancer treatment to the less proximate outcome of early menopause in the years to decades after treatment. A woman's reproductive lifespan can be shortened after chemotherapy or radiation because such treatments likely decrease the number of viable eggs after treatment. This acceleration in the decline of the number of follicles leads to increased rates of not only infertility and miscarriage but also early menopause, which represents the most extreme form of accelerated ovarian aging. The degree of reproductive impairment is dependent on chronologic age and the diagnosis or treatment. The variation in outcomes that persist may be partially explained by pretreatment ovarian reserve. Establishing the use of clinical predictors such as ovarian reserve markers to effectively anticipate such outcomes is an obvious and important keystone in the foundation of cancer survivorship research. An improved understanding of cancer treatment's ability to accelerate follicle death, decrease fecundability, and initiate an earlier menopause could provide a clinically relevant, time-shortened, and reproducible snapshot into the basic biology of ovarian aging.
Keywords: cancer; ovarian reserve; ovarian age; menopause; ovarian failure; chemotherapy; radiation